Performance of a pilot-scale biofilters and constructed wetland with ornamental plants in greywater treatment - Ling, TY; Kasing, Apun; Siti Rubiah, Zainuddin (IDOSI, 2009)
Partially treated black water from septic tanks and grey water from households in Kuching City were polluting the Sarawak River. A pilot scale ecological sanitation was implemented where blackwater was held in septic tanks and greywater was channeled to a grease trap, biofilters and a constructed wetland before discharge. The objectives of this study were to evaluate the efficiency of the biofilters and the constructed wetland with two species of terrestrial ornamental plants in greywater treatment. For the combined system, results indicated that the influent dissolved oxygen of below 1 mg/L improved to 3.4-4.6 mg/L. Removal of biochemical oxygen demand (BOD ) and chemical oxygen demand (COD) were the highest (99 and 95%). 5 Influent fecal coliform (FC) of 4.0x105 CFU/100mL dropped to 6.3x102 CFU/100mL at the effluent. More than 80% of ammonia-nitrogen (NH -N), total nitrogen (TN) and total suspended solids (TSS) were removed. Reactive 4 phosphorus (RP) and total phosphorus (TP) removals were 64 and 61% respectively. The biofilters contributed most of the total removal of BOD , COD, FC and NH -N. However, the wetland and biofillters were equally 5 4 efficient in TSS removal. The removal efficiency of the wetland in decreasing order was NO -N>FC> 3 TSS>BOD >TN>COD>NH -N>RP>TP and all removals exceeded 55% with the exception of P (38-39%). Both 5 4 species of plants grown on the wetland contained significantly higher weight and P content than the control. Tissue P content of F. microcarpa was significantly higher than S. campanulatum indicating F. microcarpa as a better accumulator of P. This indicates that constructed wetland with F. microcarpa could be potentially implemented in urban housing areas to reduce river pollution.